Assessment of cerebral perfusion and edema in preeclampsia with intravoxel incoherent motion MRI. (12th June 2018) - Nelander, Maria; Hannsberger, Daniel; Sundström‐Poromaa, Inger; Bergman, Lina; Weis, Jan; Åkerud, Helena; Wikström, Johan; Wikström, Anna‐Karin
Abstract: Introduction: Cerebral complications are the main reasons for morbidity and mortality in preeclampsia and eclampsia. As yet, we do not know whether the pathophysiology entails hypo‐ or hyperperfusion of the brain, or how and when edema emerges, due to the difficulty of examining the cerebral circulation. Material and methods: We have used a non‐invasive diffusion weighted‐magnetic resonance imaging technique, intravoxel incoherent motion, to study cerebral perfusion on the capillary level and cerebral edema in women with preeclampsia (n = 30), normal pregnancy (n = 32), and non‐pregnant women (n = 16). Estimates of cerebral blood volume, blood flow, and edema were measured in 5 different regions. These points were chosen to represent blood supply areas of both the carotid and vertebrobasilar arteries, and to include both white and gray matter. Results: Except for the caudate nucleus, we did not detect any differences in cerebral perfusion measures on a group level. In the caudate nucleus, we found lower cerebral blood volume and lower blood flow in preeclampsia than in either normal pregnancy ( P = .01 and P = .03, respectively) or non‐pregnant women (both P = .02). No differences in edema were detected between study groups. Conclusion: The cerebral perfusion measures were comparable between the study groups, except for a portion of the basal ganglia where hypoperfusion was detected in preeclampsia but not in normal pregnancy or non‐pregnant women.